FRI0077 Levels of mir-16 in serum associate with response to therapy in patients with early rheumatoid arthritis. (23rd January 2014) - Filkova, M.; Ospelt, C.; Vettori, S.; Šenolt, L.; Mann, H.; Vencovský, J.; Pavelka, K.; Michel, B. A.; Gay, R. E.; Gay, S.; Jüngel, A.
Abstract : Background: Studies have shown a beneficial effect of early treatment on clinical outcome and reduction in joint damage in patients with rheumatoid arthritis (RA). MiRNAs are stably present in cell-free form in body fluids and circulating miRNAs are becoming new candidate biomarkers for diagnosis and prognosis in different diseases. MiR-16 was shown to be of higher expression in synovial fluids and peripheral blood mononuclear cells in patients with RA compared with osteoarthritis (Murata et al. 2010, Pauley et al. 2008). Objectives: To analyze miR-16 in sera of patients with early RA (ERA) to find a tool to monitor disease outcome. Methods: Total RNA was isolated using phenol-chloroform extraction from sera of patients with ERA (n=34, disease duration <8 months) before and after 3 months therapy with disease modifying antirheumatic drugs (DMARDs, methotrexate n=28, sulphasalazine n=4, leflunomide n=1) and glucocorticoids (n=30) as well as from patients with established RA (n=28, disease duration 9.28±6.52 years) treated with DMARDs (methotrexate n=14, sulphasalazine n=2, leflunomide n=8), glucocorticoids (n=6) or biologics (n=19). Clinical characteristics of ERA patients were assessed at baseline and after 3, and 12 months therapy. MiR-16 and let-7a, which was used as a normalization control, were reverse transcribed using specific primers with equal input of 12.5ng RNA and analyzed by TaqMan Real-Time PCR. Delta Ct method was used for relative quantification (dCt = Ct let-7a - Ct miR-16). Results: MiR-16 was found at significantly lower levels in sera of patients with ERA before treatment (dCt 4.93±0.91) than in patients with established RA (dCt 6.10±1.22, p<0.001). After 3 months treatment with DMARDs, circulating miR-16 significantly increased in ERA sera in comparison with baseline (dCt 4.93±0.91 vs. 5.71±1.27, p=0.007). Baseline levels of miR-16 correlated with the change in DAS28 from baseline to 3 months follow up (r=-0.478, p=0.008): patients with low levels of miR-16 at baseline showed only a small decrease in DAS28 while patients with high levels of miR-16 at baseline showed a greater improvement in disease outcome from baseline to 3 months follow up. Similarly, the levels of miR-16 at 3 months follow up correlated with a change in disease activity DAS28 from 3 months to 12 months follow up (r=-0.355, p=0.047). Importantly, the change in levels of miR-16 from baseline to 3 months follow up was negatively associated with the change in DAS28 from 3 to 12 months follow up (r=-0.519, p=0.002) suggesting that the increase in circulating miR-16 within first 3 months after treatment initiation was followed by the decrease in disease activity in the subsequent 9 months. Conclusions: Analysis of levels of miR-16 in sera may become a novel tool to monitor disease outcome and thereby a response to therapy in patients with ERA. Acknowledgements: This work was supported by IMI BTCure, IAR, Masterswitch-PF7, Articulum and MH CR project No.023728. Disclosure of Interest: None Declared